2003
DOI: 10.1093/ptj/83.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of Upper-Extremity Volume Estimates: Comparison of Calculated Volume Derived From Girth Measurements and Water Displacement Volume

Abstract: Background and Purpose. The volume of all limbs can be determined by water displacement methods or calculations derived from girth measurements. The purpose of this study was to determine the concurrent validity of calculated volume and water displacement volume measurements. Subjects. Both upper extremities of 14 women with lymphedema were measured. Methods. Volumetric measurements were taken with a volumeter, and circumferential measurements were taken with a tape measure. Calculated volume was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(119 citation statements)
references
References 21 publications
1
102
0
12
Order By: Relevance
“…The arm total volume is then determined by the sum of all segment volumes. This method of estimating limb volume has been extensively tested and validated (Casley-Smith, 1994;Latchford & Casley-Smith, 1997;Mayrovitz et al, 2000aMayrovitz et al, ,b, 2007aKarges et al, 2003;Mayrovitz, 2003). For comparison purposes, arms were designated as either dominant or nondominant depending on the handedness of the subject.…”
Section: Arm Volume Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arm total volume is then determined by the sum of all segment volumes. This method of estimating limb volume has been extensively tested and validated (Casley-Smith, 1994;Latchford & Casley-Smith, 1997;Mayrovitz et al, 2000aMayrovitz et al, ,b, 2007aKarges et al, 2003;Mayrovitz, 2003). For comparison purposes, arms were designated as either dominant or nondominant depending on the handedness of the subject.…”
Section: Arm Volume Measurementsmentioning
confidence: 99%
“…A variety of methods are available to assess overall limb oedema. These include metric and volume measures (Casley-Smith, 1994;Sander et al, 2002;Karges et al, 2003;Mayrovitz, 2003;Meijer et al, 2004;Mayrovitz et al, 2005Mayrovitz et al, , 2006Mayrovitz et al, , 2007a, automated methods (Mayrovitz et al, 2000b;Moseley et al, 2002;Stanton et al, 1997;Tierney et al, 1996) and electrical impedance-type methods (Cornish et al, 1998(Cornish et al, , 2001(Cornish et al, , 2002Ward, 2006). However, these methods are not generally suitable to determine local oedema or oedema in body parts other than the limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods are expensive and not regularly accessible for physical therapists while limb circumference and water displacement measurements are common in physical therapy practice (Casley-Smith, 1994;Stizia, 1995;Boland & Adams, 1996;Perrin & Guex, 2000). Limb volume measurements by girth measurements or water displacement are both reliable and highly correlated but not interchangeable (Sander et al, 2002;Karges et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The limb circumferential measures have been demonstrated to be reliable and reproducible in the literature. 15,19,[26][27][28][29] We have recently performed studies with volumetric measurement using CT scans and have found statistically significant correlation between circumferential measurements and CT volumetric measurements (under submission).…”
Section: Case 3: Kt Syndromementioning
confidence: 99%